The identity of Aplocheilus andamanicus (Köhler, 1906) (Teleostei: Cyprinodontiformes), an endemic Killifish from the Andaman Islands, with notes on Odontopsis armata van Hasselt - Katwate, Unmesh; Kumkar, Pradeep; Britz, Ralf; Raghavan, Rajeev; Dahanukar, Neelesh (Zootaxa, 2018)
In his work on the fishes of the Andaman Islands, Francis Day (1870) collected large-sized specimens of Aplocheilus from the south Andamans. Despite differences in the size and dorsal-fin ray counts, Day refrained from recognising the Andaman Aplocheilus as a distinct species and considered it as Aplocheilus panchax, a species distributed in the Ganges delta and across the eastern coast of mainland India. However, Day mentioned the differences in fin-ray counts between these two populations. Subsequently Köhler (1906) described the Andaman population as Haplochilus andamanicus (now in Aplocheilus), referring to the diagnostic characters initially discovered by Day. This species failed to receive recognition from taxonomists, because of the uncertainty regarding the validity of the species and its questionable synonymy with A. panchax. In this study, based on morphological and molecular evidence, we demonstrate that A. andamanicus is indeed a distinct and valid species, which can easily be diagnosed from the widespread A. panchax. While resolving the identity of A. andamanicus, we also demonstrate that the congeners from southeast Asia form a genetically distinct group for which the name Odontopsis armata is available.